Levofloxacin loaded PMMA:PVP blended nanofiber mat as an antibacterial material - V A Karachevtsev; A M Plokhotnichenko; O V Trufanov; S G Stepanian (Materials Research Express)
Polymeric nanofibers loaded with antibacterial agents occupy a leading position among many technologies for producing antibacterial materials due to their unique properties. In this work, a novel electrospun nanofiber mat loaded with antibacterial antibiotic levofloxacin (LV) was developed using a blend of hydrophilic (polyvinylpyrrolidone (PVP)) and hydrophobic (polymethyl methacrylate (PMMA)) polymers. The diameter of the obtained nanofibers is in the range of 1–4 μm. The release of LV from the nanofiber mat after soaking in water was studied by UV–vis absorption spectroscopy. PVP facilitates the incorporation of antibacterial agents into the nanofibers and promotes their release in the aqueous solution. From the temporal dependence of LV release from PMMA:PVP blend nanofibers follows that about half of the LV is released into aqueous solution during the first 5 min while the other 1/4 of the LV is released during the next 2–3 h. A complete release of LV from PMMA nanofibers is not observed because a certain part of the nanopores is closed. The formation of non-covalent complexes between LV and PVP was examined within the framework of quantum chemical theory. A tetrameric model of vinylpyrrolidone was employed to simulate interactions with LV. The most stable complex was identified, with an interaction energy of –58.9 kJ mol ^−1 . These findings suggest that such molecular complexation may have an impact on the drug release behavior. In the nanofiber mat, PMMA promotes the gradual release of antibacterial drug, and does not degrade upon contact with water and/or with microorganisms. The PMMA:PVP blended nanofiber mat can serve as an effective delivery system for the antibiotic LV, maintaining its bactericidal effects, as evidenced by the growth inhibition of both Gram-positive and Gram-negative bacteria. It was found that the LV released from the nanofiber mat more strongly inhibited the growth of E. coli B compared to S. aureus and P. aeruginosa .